2009
DOI: 10.1007/s10654-009-9346-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyl transferase level and diabetes mellitus among US adults

Abstract: Serum gamma-glutamyl transferase (GGT), a marker of oxidative stress, has been shown to be associated with diabetes mellitus in some population-based studies, but not all. Also, it is not clear if there is a continuous dose-response relationship in this association, or if this association is evident only beyond a particular threshold level of GGT. We examined the association between serum GGT and diabetes mellitus in a representative sample of US adults aged > or = 20 years, in a cross-sectional study involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 20 publications
5
23
0
Order By: Relevance
“…In good agreement with data of Framingham Offspring Study [2], Kaushik et al reported that serum GGT markedly correlated with body weight and BMI in obese children with diabetic mother [18]. Lee et al showed that there was an increase in hazard ratios of incident diabetes for people with higher serum GGT concentrations after a 15-year of follow-up [32], which was consistent with a survey conducted by Sabanagam et al [33]. Likewise, a study from Iran found that serum GGT was a predictor of diabetes for the first-degree relatives of diabetes [34].…”
Section: Discussionsupporting
confidence: 84%
“…In good agreement with data of Framingham Offspring Study [2], Kaushik et al reported that serum GGT markedly correlated with body weight and BMI in obese children with diabetic mother [18]. Lee et al showed that there was an increase in hazard ratios of incident diabetes for people with higher serum GGT concentrations after a 15-year of follow-up [32], which was consistent with a survey conducted by Sabanagam et al [33]. Likewise, a study from Iran found that serum GGT was a predictor of diabetes for the first-degree relatives of diabetes [34].…”
Section: Discussionsupporting
confidence: 84%
“…A study by Hull et al (1997) showed that children with CF and pulmonary inflammation had higher GGT activity and lipid peroxide concentrations and lower glutathione concentrations in bronchiolar lavage fluid than did CF patients without inflammation or non-CF control subjects. Recently, increased serum GGT activity has been associated with development of atherosclerosis and cardiovascular disease (Emdin et al, 2005;Meisinger et al, 2006;Shankar et al, 2008) and their risk factors, including diabetes (André et al, 2006), hypertension (Sabanayagam et al, 2009), dyslipidemia and metabolic syndrome (Rantala et al, 2000;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several prospective studies and meta-analyses suggested that gamma-glutamyltransferase (GGT), a previously recognized marker of alcoholic drinking and fatty liver, could predict the risk of T2D [13]. Such an association existed even when GGT was at physiologic level [4], in nonalcoholic drinkers and subjects without nonalcoholic fatty liver disease (NAFLD) [5, 6]. One study suggested that BMI could predict T2D only when GGT was at physiologic high levels [7].…”
Section: Introductionmentioning
confidence: 99%